Assessment of supracrestal tissue attachment variation in patients with chronic periodontitis before and after treatment: A clinical-radiographic study - Saquib, Shahabe; Anoop, Gore; Dani, Nitin; Ashfaque, Yaqoob; Khan, Abdul Ahad; Attar, Nilofer; Al-qahatani, Saad (Vojnosanitetski pregled, 2020)
Background/Aim. Healthy periodontium comprises the dento-gingival junction. Periodontal disease starts to appear when the integrity of the junctional epithelium is disturbed. Assessment of the supracrestal tissue attachment (SCTA) is essential because there is a frequent need for restoration or prosthesis after periodontal surgical and non-surgical therapy. The aim of the present study was to evaluate the SCTA variations in a patients with chronic periodontitis before and after treatment. Methods. Thirty systemically healthy patients with periodontitis were enrolled in the study. Fifteen patients were subjected to scaling and root planing and 15 to open flap debridement. Radiographic and clinical findings of the SCTA were assessed before and after treatment at 3-month and 6-month intervals. Results. Comparison between clinical and radiographic findings of the SCTA showed a significant difference in patients with periodontitis (p  0.05), but showed a significant difference in patients with moderate pockets treated by open flap debridement (p
Keywords: periodontics; debridement; surgical flaps; gingival recession; dental scaling; radiography, dental